Assessment of the potentially toxic element contamination in water of Şehriban Stream (Black Sea Region, Turkey) by using statistical and ecological indicators - Tokatli, Cem; Mutlu, Ekrem; Arslan, Naime (Wiley, 2021)
AbstractIn the present study, the spatial–temporal variations of iron, lead, copper, cadmium, mercury, nickel, and zinc accumulations in the water of Şehriban Stream (northern Turkey) were investigated. Water Quality Index (WQI), Heavy Metal Evaluation Index (HEI), Pearson Correlation Index (PCI), and Factor Analysis (FA) were used in analyzing the water quality. Sampling was performed in 12 stations on monthly basis between February 2019 and January 2020 (a hydrological year). The data showed that the Şehriban Stream had significantly high water quality characteristics and the investigated toxicants were not found as dangerous for health. Although there was a slight decrease in the water quality from upstream to downstream, the stream was found to have 1st class water quality in general. As a result of WQI and HEI, although it was determined that the water quality decreased slightly in autumn, the stream was found to be “A Grade – Excellent (<50)” and “Low Contamination (<10),” respectively. As a result of PCI, strong positive correlations were found between almost all the toxicants investigated here (p < 0.01). As a result of FA, 2 factors (“Agriculture – Forestry” and “Rock Structure”) explained 86% of the total variance.
Keywords: Turkey; Multivariate-Analysis; Quality Index; Surface-Water; Metals, Heavy; Water Quality; Water Quality Index; Dissolved Trace-Elements; Potentially Toxic Elements; River; Basin Turkey; Heavy-Metals; Groundwater Quality; Water; Sediment Quality; Black Sea; Heavy Metal Evaluation Index; Ş Ehriban Stream; Factor Analysis; Health-Risk Assessment; Water Pollutants, Chemical; Environmental Monitoring; 14. Life underwater; 6. Clean water; 13. Climate action